Hubungan Body Image, Kebiasaan Makan, dan Status Gizi dengan Masalah Anemia Gizi pada Remaja Putri di SMA Negeri 1 Sampang - Widya Indina Zulfa (Media Gizi Kesmas, 2023)
Background: Anemia is a condition where blood cell count or oxygen capacity does not adequately meet physiological needs. Factors that cause anemia in young women are abnormal menstrual patterns and also lack of knowledge about anemia and nutritional status. Objectives: The purpose of this study was to analyze the relationship between body image, eating habits, and nutritional status with anemia problems in young women at SMA Negeri 1 Sampang.. Methods: The research design used is a cross-setional study. The variables studied were body image perception, eating habits, nutritional status, and anemia status. The research sample was a student at SMA Negeri 1 Sampang in the tenth and eleventh grades. Results: The results showed that there was no significant relationship with body image (p-value=0.562), frequency of eating (p-value of staple food consumption=0.502, p-value of animal side dish consumption=0.951, p-value of vegetable side dish consumption=0.220, p-value of vegetable consumption=0.263, p-value of fruit consumption=0.769, p-value of consumption of other foodstuffs=0.751), breakfast habits (p-value=0.686), energy intake (p-value=0.563), protein (p-value=0.537), iron (p-value=0.648), folate (p-value=0.221), Vitamin C (p-value=1.000), Vitamin B12 (p-value=0.146), Vitamin B6 (p-value=0.831), and zinc (p-value=0.731) with anemia status, there is a relationship between nutritional status and anemia (p value=0.004). Conclusions: This study did not have a significant relationship between body image with anemia, frequency of eating with anemia, energy intake, protein, fe, folate, Vitamin C, Vitamin B12, zinc, and Vitamin B6 with anemia. There is a significant association between nutritional status and anemia